Cross-Linking/Mass Spectrometry Uncovers Details of Insulin-Like Growth Factor Interaction With Insect Insulin Binding Protein Imp-L2 - Pompach, Petr; Viola, Cristina M.; Radosavljević, Jelena; Lin, Jingjing; Jiráček, Jiří; Brzozowski, Andrzej M.; Selicharová, Irena (Frontiers in Endocrinology, 2019)
Structural details of changes accompanying interaction between insulin-related hormones and their binding partners are often enigmatic. Here, cross-linking/mass spectrometry could complement structural techniques and reveal details of these protein-protein interfaces. We used such approach to clarify missing structural description of the interface in human insulin-like growth factor (IGF-1):Drosophila melanogaster imaginal morphogenesis protein-late 2 protein (Imp-L2) complex which we studied previously by X-ray crystallography. We crosslinked these proteins by heterobifunctional cross-linker sulfosuccinimidyl 4,4’-azidopentanoate (Sulfo-SDA) for the subsequent mass spectrometry (MS) analysis. The MS analysis revealed IGF-1:Imp-L2 interactions which were not resolved in the crystal structure of this assembly, and they converged with X-ray results, indicating the importance of the IGF-1 N-terminus interaction with the C-terminal (185-242) part of the Imp-L2 for stability of this complex. Here, we also showed the advantage and reliability of MS approach in solving details of protein-protein interactions that are too flexible for solid state structural methods.